Zur Phosphatbelastung von Rhein und Mosel - Hellmann, Hubert; Schuhmacher, Manfred (ERDKUNDE, 1979)
The phosphate load of German surface waters increased greatly over the period 1962-1973. Taking the middle Rhine and Moselle as examples, the hydrological interpretation and evaluation of measurement results are discussed with particular emphasis on the problem of the origin of loads and of the trend. Prognoses are made possible with the help of EDV.